Efectos de un programa de investigación acción participativa sobre el liderazgo situacional y los estilos de aprendizaje en universitarios de Lima metropolitana - Franco Mendoza, Josué Michael (2021)
The main objective of the present study was to determine the effect of a participatory action research (PAR) program, following Paredes' model (1998), on situational leadership and learning styles in university students of the psychology and education faculties in a public university in metropolitan Lima. For this purpose, 32 students from both faculties participated, among men and women, randomly divided into two groups of 16 people: one to which an emotional competence program would be applied and the other from which only pre- and post-test measures would be obtained, in the framework of an experimental design. The instruments used included the Situational Leadership Scale (Aburto, 2014) and the Learning Styles Scale (CHAEA) by Horney and Alonso. The results of the study show significant effects of the program, from the contrast of differences in the punctuations on both variables, above all in the styles of direct and participative leadership, detecting also significant correlations after the application of the program between the styles of active and pragmatic learning. It is concluded that the program evidences adequate results; however, it is recommended to extrapolate it to other groups, given the characteristics of the target audience of activities where it was developed. Key words: Situational leadership, participatory action research, learning styles.